PENERAPAN MODEL LEARNING CYCLE 7E UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMA - Dina Damayanti Siregar; Stepanus Sahala Sitompul; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to improve student learning outcomes on elasticity and Hooke's law by applying the learning cycle learning 7E model. The design of this study was in the form of a quasi-experimental design with a nonequivalent control group design. This study involved students of class XI MIA 3 and class XI MIA 4 in SMA Negeri 6 Pontianak, who were selected using a random sampling method with an intact group. Data collection tools used in the form of a test form consisting of 5 questions with a reliability level of 0.56. Based on the results of the Mann Whitney U test obtained Zcount by -4.71 and Ztable by -1.96 (-1.96 > -4.71). Thus there are differences in student learning outcomes between the group taught with the applied model, and the group taught with the conventional learning model. The effectiveness of the applied learning model was calculated using the Cohen effect size formula with the result of 1.53 and a high category. Therefore, it can be concluded that the application of the learning cycle 7E model can improve student learning outcomes on the material of elasticity and Hooke's law. Keywords: Elasticity & Hooke’s Law, Learning Cycle 7E model, Learning Outcomes.